Chief executive officer shareholding and company performance of Malaysian publicly listed companies - Heng, Soon Eng; Ong, Tze San; Teh, Boon Heng (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2016)
This study aims to investigate the relationship between chief executive officer (CEO) shareholding and company performance. Specifically, the study investigates the influence of the level of direct and indirect CEO shareholdings on the market growth, profitability and liquidity of companies. A sample comprising 59 companies was obtained from Bursa Malaysia within a five-year period from 2009 to 2013. Results reveal that most CEOs of Malaysian listed companies own company shares either directly or indirectly. The CEOs of listed companies in Malaysia tend to retain controlling stakes by possessing a significant amount of shares in their companies. As a result, these companies demonstrate improved financial performance.